Dampak Teknologi Inovatif, Word of Mouth dan Motivasi Hedonis terhadap Pemakaian Shoppe Paylater - Fitria Yoga Hestiningtyas; Linda Ayu Oktoriza (Journal of Management and Bussines (JOMB), 2024)
This research aims to analyze the influence of innovative technology, word of mouth, and hedonic motivation on people's use of Shopee Paylater in 2023. The research method uses a short study approach with primary data collection. The research results show that innovative technology does not significantly influence users' interest in using the PayLater feature in the Shopee application. However, word of mouth has a significant influence, showing that positive recommendations from other people can influence perceptions of Shopee Paylater. Apart from that, hedonic motivation also has a significant effect, indicating that enjoyment in using Shopee PayLater is an important factor in user interest in the service. In conclusion, this research provides important insights for the future development of digital financial services, by considering the factors that influence user adoption. Keywords: Hedonic, Word of Mouth, Shoppe Paylater, Innovative Technology